Gauging Change in Australian Aid: Stakeholder Perceptions of the Government Aid Program. Issue 2 (14th March 2017) - Wood, Terence; Burkot, Camilla; Howes, Stephen
Abstract: In this article, we use data from the 2013 and 2015 Australian Aid Stakeholder Surveys to gauge the extent of the changes to the Australian Government Aid Program since the 2013 federal election. The two surveys targeted the same set of stakeholders of the aid program, and both gathered data on a wide range of aspects of its functioning. As we assess the findings that emerged from the surveys, we situate our work amongst recent academic studies that have looked at the post‐2013 aid changes in Australia. Our key findings are that the post‐2013 changes to Australian aid have had wide‐ranging impacts and have led to deteriorating overall aid quality. However, changes have not affected all aspects of the aid program equally, and some changes are starting to be reversed. In discussion, we examine what these developments mean for the future of Australian aid.